2016
DOI: 10.1161/strokeaha.116.012662
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Incident Stroke

Abstract: Background and Purpose Low heart rate variability (HRV), a marker of cardiac autonomic dysfunction, has been associated with increased all-cause and cardiovascular mortality. We examined the association between reduced HRV and incident stroke in a community-based cohort. Methods The Atherosclerosis Risk in Communities (ARIC) Study measured HRV using 2-minute electrocardiogram readings in 12,550 middle-aged adults at baseline (1987-89). HRV indices were calculated using the standard deviation of RR intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Accordingly, HRV may serve as a proxy for the neurological mechanisms that guide flexible control of physiology and behavior in the context of stress ( 44 ). Through several decades’ progress in HRV research, today HRV measurement is not only an established tool in cardiology research ( 45 ) but also increasingly being used in a wide range of clinical and psychophysiological research ( 46 , 47 ), including informing cardiovascular risk stratification and ischemic stroke prediction ( 48 , 49 ). Therefore, the critical idea is that HRV may be more than just an index of cardiac function; it may act as an indicator of central modulation of global stress responses.…”
Section: Ans Measurement: Hrvmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, HRV may serve as a proxy for the neurological mechanisms that guide flexible control of physiology and behavior in the context of stress ( 44 ). Through several decades’ progress in HRV research, today HRV measurement is not only an established tool in cardiology research ( 45 ) but also increasingly being used in a wide range of clinical and psychophysiological research ( 46 , 47 ), including informing cardiovascular risk stratification and ischemic stroke prediction ( 48 , 49 ). Therefore, the critical idea is that HRV may be more than just an index of cardiac function; it may act as an indicator of central modulation of global stress responses.…”
Section: Ans Measurement: Hrvmentioning
confidence: 99%
“…Impaired autonomic function is likely to be a common feature in all ischemic stroke patients ( 52 , 53 ). Earlier findings showed that: (i) lower HF and/or total power was correlated with a higher risk of incident stroke in adults ( 49 ); (ii) other HRV parameters such as dichotomized coefficient of variance of NN intervals (CV%) and power law slope (SLOPE) may also stratify high-risk patients to develop stroke, with 0.68 c-statistic for combined high CV% and high SLOPE ( 54 ); (iii) patients with ischemic stroke irrespective of the side of the ischemia in the brain had dysfunctional ANS and decreased HRV [HF, LF and total power (TP)] compared to healthy controls ( 50 , 55 ); (iv) certain locations of stroke, such as right insular stroke, right middle cerebral artery stroke, and parietal or frontal lobe stroke, were correlated with higher risks of cardiac dysfunction ( 56 ), atrial fibrillation (AF) ( 52 , 56 ), and myocardial injury ( 57 ), compared to other sites; (v) acute large strokes, because of the huge stress and catecholamine release, were more likely to cause cardiac dysfunction compared to lacunar strokes; and (vi) poststroke decreased HRV was associated with stroke severity, incidence of early and late complications, and mortality ( 47 , 58 ). The potential therapeutic effects of parasympathetic activation on ischemic stroke have also been documented ( 59 , 60 ).…”
Section: Ans Dysfunction Impaired Hrv and Risk Factors Of Ischemicmentioning
confidence: 99%
“…In the Atherosclerosis Risk in Communities study, HRV was measured in 12,550 middle-aged adults, and Cox regression analysis showed a significant and strong association of reduced HRV parameters with a modest risk of incident stroke in adults with diabetes mellitus, irrespective of traditional cardiovascular risk factors (57). These previous studies also demonstrated that decreased HRV precedes poor outcome, suggesting that low HRV may be an early indicator of declining health in populations already at high risk.…”
Section: Use Of Hrv For Stratifying the Risk Of Strokementioning
confidence: 89%
“…[17] Cerebrovascular hemodynamics, which is called circulatory autoregulation are essential for the brain. [24] Slow blood pressure and flow changes are physiologically controlled by the sympathetic nervous system, therefore, it is possible that abnormal DC triggers changes in cerebral vascular pressure and flow. [25] In a rapid pacing AF model, atrial myocardium has significant and inhomogeneous neuronal eruption and sympathetic over-distribution.…”
Section: Discussionmentioning
confidence: 99%